Role of particle size distribution of bridging agent for drilling mud on formation damage near wellbore. (2021) - Ismail, N.I.; Lawrence, E.; Naz, M.Y.; Shukrullah, S.; Sulaiman, S.A.
Abstract: One of the most important aspects of drilling mud is the optimization of particle size of bridging agent. The bridging agent is deliberately sized to minimize the fluid loss into the reservoir and to control the permeability near the wellbore. The objective of this study is to visualize the invasion depth of drilling mud particles into the formation and to evaluate the effects of bridging agent particle size and distribution on permeability and porosity near wellbore. Calcium carbonate was used as a bridging agent. It is important to know the severity of formation damage caused by the drilling mud to attain maximum production over a long period of time. This paper describes an experimental approach to study the effects of bridging agent particles in drilling mud on formation damages. The work was performed by changing the size of bridging agent particles from fine to medium and medium to coarse. It was observed that the calcium carbonate size should be almost identical to the pore throat median size of the formation face. The minimum reduction in permeability was noticed when pore spaces were covered with bridging particles, which prevent the fluid loss into the formation.